Advancing ASO therapies from development to implementation - Schüle-Freyer, Rebecca; Synofzik, Matthis; Graessner, Holm; Aartsma-Rus, Annemieke (Nature medicine, 2024)
A novel application of antisense oligonucleotide (ASO) technology, developed to treat a single patient, adds to the growing number of ‘personalized’ therapies for rare diseases; but pathways to implementation and access are urgently needed.
Gesehen am 10.04.2025